Perilaku Aktivitas Fisik dan Determinannya pada Mahasiswa Fakultas Ilmu - Ilmu Kesehatan Universitas Muhammadiyah Prof. Dr. Hamka - Yoli Farradika; Yuyun Umniyatun; Mochamad Iqbal Nurmansyah; Miftahul Jannah (ARKESMAS [Arsip Kesehatan Masyarakat], 2019)
ABSTRACT Based on data from the 2013 Basic Health Research (Riskesdas) groups of adolescents to young adults (15-24) have sedentary lifestyles (sedentary / lack of physical activity) of 52%. Lack of physical activity can lead to health risks especially the complications of non-communicable diseases such as obesity, diabetes, hypertension and heart problems. This study aims to determine the relationship of physical activity and its determinants. This study uses a quantitative method with a cross-sectional study design. A total of 846 FIKES UHAMKA students participated in this study. Data collected by filling out the questionnaire by students. Data analysis used the chi square test to determine the relationship between physical activity and its determinants and logistic regression to determine the predictors of physical activity. This study provides results that the average Metabolic Equivalent (MET) score is 1420.33 ± 2384.297. Respondents who have low physical activity by 47.8%, moderate physical activity by 39.6% and high physical activity by only 12.6% of respondents. There is a significant relationship between gender, work status, availability of sports facilities, lecturer support, and perception of sports on physical activity. Active physical activity is more common in male sex respondents, students who are already working, the availability of sports facilities at home or the surrounding environment, the invitation of lecturers to exercise and a good perception of sports. The results also showed that respondents who did not work, did not have sports facilities at home, and had a poor perception of sports were predictors of having passive / mild physical activity. Keywords : Perception, Attitude, Environment, Sports Facilities, Physical Activity of Students